2014
DOI: 10.1095/biolreprod.113.113068
|View full text |Cite
|
Sign up to set email alerts
|

Cell Density-Mediated Pericellular Hypoxia and the Local Dynamic Regulation of VEGF-A Splice Variants in Ovine Ovarian Granulosa Cells1

Abstract: The primary aims of this study were to utilize a specialized culture system to further elucidate the functional significance of pericellular hypoxia within the granulosa cell (GC) compartment of growing follicles, and to clarify its effects on the production of vascular endothelial growth factor (VEGF)-A isoforms and steroid hormones. Multilaminar clusters formed rapidly in ovine GCs seeded at high density (HD), and Hypoxyprobe-1 protein adducts appeared markedly more abundant and HIF-1 activation significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…In HT-29 cells, HIF-1α levels were not significantly increased with an increase in cell density. We hypothesized that the HIF-1α accumulation induced by pericellular hypoxia might already be present in HT-29 cells because of their aggregated form [ 35 ]. The comparatively slight increase in the ROS level in HT-29 cells with the increase in cell density can also be interpreted in this scheme.…”
Section: Discussionmentioning
confidence: 99%
“…In HT-29 cells, HIF-1α levels were not significantly increased with an increase in cell density. We hypothesized that the HIF-1α accumulation induced by pericellular hypoxia might already be present in HT-29 cells because of their aggregated form [ 35 ]. The comparatively slight increase in the ROS level in HT-29 cells with the increase in cell density can also be interpreted in this scheme.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear whether hypoxia is an essential signal during the folliculo-luteal transition [ 11 ]. As for granulosa cells (GC) it was proposed that pericellular hypoxia present under high cell density conditions may induce differentiation [ 12 ]. Likewise, we showed that high cell density induces specific changes of the gene expression and steroid hormone profiles in cultured GC mimicking an early post-LH status of GC differentiation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%